2011
DOI: 10.5897/ajpp11.242
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoepidemiological studies of prescribing practices of health care providers of Pakistan: A cross-sectional survey

Abstract: Half of all medicines are prescribed or sold inappropriately and half of all patients fail to take their medicines correctly worldwide. The present study was conducted to evaluate the pattern and practice of drugs within the modern medical system by investigating the prescription pattern, drug use in private and public health care facilities, assessment of the magnitude of the problem, identifying factors responsible for the problem, suggesting measures in Pakistan. There were marked differences between the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
(16 reference statements)
2
14
0
Order By: Relevance
“…Similar findings were reported from Peru and Bangladesh, where pharmacists prescribed antibiotics much more commonly than doctors [38,39]. In Pakistan, surveys reported that Government doctors advised less antibiotics and laboratory tests than private practitioners [31,40].…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings were reported from Peru and Bangladesh, where pharmacists prescribed antibiotics much more commonly than doctors [38,39]. In Pakistan, surveys reported that Government doctors advised less antibiotics and laboratory tests than private practitioners [31,40].…”
Section: Discussionsupporting
confidence: 79%
“…Rational fluid therapy was significantly predicted by best knowledge regarding diarrheal signs/symptoms, occurrence/spread, prevention/control and ORS. Physicians’ knowledge and other patient related factors were found to have strong correlations in other studies also [ 3 , 32 , 57 ].…”
Section: Discussionmentioning
confidence: 59%
“…Longer duration of practice was associated with higher odds of rational antibiotic use in case of watery/bloody diarrhea. An exploratory research involving physicians in peri-urban area of Lima, Peru previously illustrated that length of practice was an important predictor of appropriate prescription habit among practitioners [ 53 ] while some other studies also reported similar influence of practitioners’ experience on management practices [ 3 , 40 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This will enhance appropriate prescribing as well as prescribers' and dispensers' knowledge of the prescribing process and formulary management. Alongside this, the development, distribution and monitoring of physician adherence to STGs for high priority disease areas [32]. The WHO provides good guidance on how to establish DTCs,[103] and the experience in Stockholm, Sweden, and other countries suggests that trusted physicians should be a key element in the development of formularies and prescribing guidance to enhance subsequent adherence [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Alongside this, the development, distribution and monitoring of physician adherence to STGs for high priority disease areas. [32] The WHO provides good guidance on how to establish DTCs, [103] and the experience in Stockholm, Sweden, and other countries suggests that trusted physicians should be a key element in the development of formularies and prescribing guidance to enhance subsequent adherence. [18,19] Such activities should be undertaken alongside instigating continuous medical education and continuous professional development for physicians surrounding an agreed list of prescribed drugs.…”
Section: Discussionmentioning
confidence: 99%